2019
DOI: 10.1053/j.gastro.2018.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Incidence of Young-Onset Colorectal Cancer and Patient Survival

Abstract: From 1992-1996 [ ] to 2010-2014 [ ], increases in young-onset colorectal cancer have been largely due to increases in rectal cancer, especially in whites. In the most time recent period, blacks and whites have similar incidence and survival of rectal cancer, a sharp contrast to the striking disparities in colon cancer. 1 1.5 2 2.5 3 3.5 4 4.5 5 30 40 50 60 70 80 90 100 Whites, rectum Blacks, rectum Whites, distal colon Blacks, distal colon Whites, proximal colon Blacks, proximal colon Incidence per 100,000 Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
107
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 64 publications
6
107
1
Order By: Relevance
“…Increasing rates of rectal (vs proximal colon) cancer have largely driven increasing incidence of early-onset CRC, particularly among whites. 7 Rectal cancer increased by 80% from the early 1990s through 2015 (from 2.6 to 4.7 per 100,000), 3,5 compared with an increase of about 40% in colon cancer. Differences in incidence by anatomic subsite Figure 1.…”
Section: Introductory Lecturesmentioning
confidence: 99%
“…Increasing rates of rectal (vs proximal colon) cancer have largely driven increasing incidence of early-onset CRC, particularly among whites. 7 Rectal cancer increased by 80% from the early 1990s through 2015 (from 2.6 to 4.7 per 100,000), 3,5 compared with an increase of about 40% in colon cancer. Differences in incidence by anatomic subsite Figure 1.…”
Section: Introductory Lecturesmentioning
confidence: 99%
“…To the best of our knowledge, previous studies have not taken these features into account when evaluating the incidence and survival rates of these two cancers. Racial disparities of incidence and survival rates were well documented in several common carcinomas such as malignant meningioma, hepatocellular carcinoma, uterine corpus carcinoma, prostate carcinoma, and pancreatic carcinoma (6)(7)(8)(9)(10)(11). However, little is known about the racial disparities in the incidence and survival rates of vulvar and vaginal carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, CRC racial health disparity remains profound despite improved CRC screening in AA patients. (3)(4)(5)(6)(7)(8) Growing evidence has demonstrated that CRC in AAs has unfavorable tumor biology. A 2018 study by Sineshaw and colleagues using the National Cancer Database found that while access to care and tumor stage accounted for three quarters of the AA-EA survival disparity in patients under 65, fully 25% of the survival difference remains unexplained by these factors suggesting that tumor biology and immune factors may play a role in this disparity.…”
Section: Introductionmentioning
confidence: 99%